2018
DOI: 10.5334/ijic.4174
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Integrated Care in Singapore: A Complex Adaptive System Perspective

Abstract: Background:Integrated care that focuses on organising healthcare services around people and their communities rather than their diseases is promoted as the strategy to overcome the challenges associated with growing complexity in healthcare needs, demand for healthcare services and inadequate supply of services due to fragmentation in the provision of services. While conceptually appears to be simple, integrated care is made up of multicomponent delivery strategies targeting various levels of the healthcare sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 18 publications
2
39
0
Order By: Relevance
“…System wide changes to processes and structures and targeted allocation of resources are required to achieve integration of care across various health sectors [38]. As observed in other healthcare integration programs [39], the size and complexity of the WSICP were noted by our respondents who, whilst agreeing that systemic changes were occurring, suggested that such change requires a sustained long term effort.…”
Section: Discussionsupporting
confidence: 52%
“…System wide changes to processes and structures and targeted allocation of resources are required to achieve integration of care across various health sectors [38]. As observed in other healthcare integration programs [39], the size and complexity of the WSICP were noted by our respondents who, whilst agreeing that systemic changes were occurring, suggested that such change requires a sustained long term effort.…”
Section: Discussionsupporting
confidence: 52%
“…In order to improve collaboration between different stakeholders, the complex adaptive system perspective can be adopted to inform understanding of relationships and dependencies between different parts of the program [36]. This needs to account for the lack of homogeneity and conformity, and the difficulties in designing an optimal system in advance, given the many moving parts.…”
Section: Recommendationsmentioning
confidence: 99%
“…Other high bed number countries include Austria (intercept 1350) and Germany (1320), hence while the average for developed countries is a helpful benchmark it is important to realize that countries with high levels of integrated care such as Sweden (intercept 800), Singapore and New Zealand (790) operate with around 40% fewer beds that the developed countries average (Figure ). However, such levels of bed provision are only achieved after many years of effort enabled by government policy . Australia is generally not considered to have a highly integrated health care service, and hence bed provision lies near to the International average for developed countries.…”
Section: Discussionmentioning
confidence: 99%